2022
DOI: 10.1055/s-0042-1749662
|View full text |Cite
|
Sign up to set email alerts
|

Giant Prolactinoma Embedded by Pseudoaneurysm of the Cavernous Carotid Artery Treated with a Tailored Therapeutic Scheme

Abstract: The coexistence of intracranial aneurysm (IA) is generally thought to be highest in patients with pituitary adenomas (PAs). Different mechanisms may play a role in aneurysm formation, but whether the PA contributes to aneurysm formation is still unclear. In the literature, there are numerous reported cases of this association; however, the analyses of the characteristics of PAs, aneurysms, and treatment management are rare and limited to a restricted number of case reports. We report a rare case of an embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Patients with PA are known to have a higher likelihood of coexisting brain aneurysms, approximately seven times greater than other types of brain tumor patients, with occurrence rates ranging from 0.5% to 7.4%. Mercuri et al reported a review of 150 cases of coexisting brain aneurysms and PA. 10) The nonsecreting type was the most common, accounting for 43% of cases, followed by GH-producing tumors at 34%. The location of the tumors was mainly in the cavernous portion, representing 71% of the cases.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Patients with PA are known to have a higher likelihood of coexisting brain aneurysms, approximately seven times greater than other types of brain tumor patients, with occurrence rates ranging from 0.5% to 7.4%. Mercuri et al reported a review of 150 cases of coexisting brain aneurysms and PA. 10) The nonsecreting type was the most common, accounting for 43% of cases, followed by GH-producing tumors at 34%. The location of the tumors was mainly in the cavernous portion, representing 71% of the cases.…”
Section: Discussionmentioning
confidence: 98%
“… 12 ) Aneurysms associated with giant prolactinomas are often partially or completely embedded within the tumor, similar to the present case, requiring an optimal treatment strategy tailored to the patient. 10 )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations demonstrated a higher incidence of intracranial aneurysms in patients harboring pituitary tumor than in the general patient population (82)(83)(84), with the circle of Willis being the most common location for aneurysm (83,85). The increased incidence of aneurysms coexisting with pituitary tumors represents the tumor-induced degenerative modification of vessel wall (85)(86)(87)(88).…”
Section: Discussionmentioning
confidence: 99%